2018
DOI: 10.1007/s00421-018-3932-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of full range of motion vs. equalized partial range of motion training on muscle architecture and mechanical properties

Abstract: These results provide evidence that crucial architectural and mechanical muscle adaptations are dependent on the ROM used in strength training. It seems that muscle FL and specific tension can be increased by pure concentric training if greater ROM is used. Conversely, restricting the ROM to shorter muscle lengths promotes a greater PCSA and angle-specific strength adaptations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…Altogether, they conclude that the contralateral training effect is real, but small (Carroll et al ). However, three previous studies showed length‐specific effects of isometric training despite using a similar design as in the present study (training simultaneously one leg short and the other leg long, for 6 weeks) (Lindh, ; Noorkoiv et al , ), furthermore a study using concentric knee extensions in partial and full ROM, also showed length‐specific effects (Valamatos et al ). Even though results of these studies argue against that the cross‐over effect would be large enough to counteract the length‐specific effects, we cannot exclude a possible minor cross‐over effect in our study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Altogether, they conclude that the contralateral training effect is real, but small (Carroll et al ). However, three previous studies showed length‐specific effects of isometric training despite using a similar design as in the present study (training simultaneously one leg short and the other leg long, for 6 weeks) (Lindh, ; Noorkoiv et al , ), furthermore a study using concentric knee extensions in partial and full ROM, also showed length‐specific effects (Valamatos et al ). Even though results of these studies argue against that the cross‐over effect would be large enough to counteract the length‐specific effects, we cannot exclude a possible minor cross‐over effect in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Most of the abovementioned studies have been conducted using isometric contractions, whereas most in vivo muscle contractions are dynamic. Despite this, only few studies have examined training response to concentric strength training at restricted muscle lengths (Graves et al ; Folland et al ; Valamatos et al ), and these studies have not examined the effects on fatigability at various muscle lengths.…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of these articles were then screened and 6 were identified as meeting inclusion criteria. [16][17][18][19][20][21] All included studies tallied 6 points on the PEDro checklist and thus were classified as being of "excellent" methodological quality. Figure 1 provides a flow chart of the search process.…”
Section: Resultsmentioning
confidence: 99%
“…All studies employed multiple set protocols, with repetitions ranging from 3 to 20 across trials; half of the included studies periodized training over the study period. 17,18,20…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies that compare the influence of concentric versus eccentric training exercises on the adaptations induced in the knee extensor muscles [33][34][35]. In general, the results point to a clear improvement in the maximum levels of force production, in an isometric regime, without being able to identify an evident advantage of one mode of training over the other [34,35].…”
Section: Introductionmentioning
confidence: 99%